Analysis of the effects of teaching units on the underqualification of mathematics teachers in secondary schools in the masina I pool - Pierre OLELA NGONGO; Jean Marie KAPENGA KAZADI NTUNDULA; Bienvenue ANAYEL NOWA; Lucien MUNSA ME TILA; KIPOPO FAUSTIN (International Journal of Scientific Research and Innovative Studies, 2026)
This study aims to analyse the effects of teaching units on underqualified mathematics teachers in schools in the Masina 1 secondary education pool. The central issue is the observation that the majority of mathematics teachers are underqualified, with an alarming proportion of them having no teacher training. The main hypothesis posits that supervision by qualified teachers could improve the pedagogical and disciplinary skills of underqualified teachers. The methodology adopted includes surveys and interviews with teachers, as well as classroom observations to assess teaching practices. The results reveal that teachers recognise the importance of mentoring. Although some resort to private consultations with qualified colleagues, the lack of a structured continuing education system remains problematic. Discussions of the results highlight the need to strengthen initial and continuing teacher training in order to improve the quality of mathematics teaching. This study highlights major challenges and calls for strategic interventions to support teachers' professional development and, consequently, student success. Keywords: teaching units, underqualified teaching, mathematics, continuing professional development, teaching difficulties. Received Date: December 20, 2025 Accepted Date: January 12, 2026 Published Date: February 01, 2026 Available Online at: https://www.ijsrisjournal.com/index.php/ojsfiles/article/view/564